Comparing Factors Affecting Indonesian and Malaysian Muslim Gen Z’s Intention to Purchase Halal Cosmetics - Rozza, Sylvia; Efriyanto, Efriyanto; Kusumawardhani, Aulia Dwi; Busono, Leksia Aura Suci (International Review of Management and Marketing, 2026)
As countries with the largest Muslim populations, Indonesia and Malaysia are committed to being the leaders of the halal cosmetics business in the world. Their government regulation stated that Muslim consumers must use halal cosmetics, while the intention to purchase halal cosmetics among Muslim Gen Z, as a massive user of cosmetics, is still low. Therefore, what should the two countries do to realize their commitment? This research aims to compare Indonesian and Malaysian Muslim Gen Z’s purchase intentions for halal cosmetics and to examine the moderating effect of their respective governments’ regulations on these intentions. The Multiple Linear Regression statistical analysis tool was applied with 120 Gen. Z Muslim respondents, each from Indonesia and Malaysia. The findings conclude that Gen Z’s intention to buy halal cosmetics is influenced by religiosity, halal awareness, price, promotion, and brand image, with government regulation also moderating this relationship. Malaysian Gen Z purchase intention is stronger than Indonesian Gen Z. It is hoped that the two countries may become the center of the global halal cosmetics industry, as Gen Z purchase intention for halal cosmetics and its sales increase. From the researchers’ knowledge, this is the first study to use this framework.